Sintesis dan Karakterisasi Polianilina Doping Asam Klorida dengan Metode Interfasial - Iman Rahayu; Annisa Wijayati; Sahrul Hidayat (Jurnal Kimia Valensi, 2015)
The growing interest in nanostructured conducting polymers is caused by expanding area of their practical application. Conducting polymers can be used in new electronic devices (transistors, displays, sensors, energy storage and memory cells), materials for shielding electromagnetic irradiation, inhibition of corrosion, membrane constructing, catalysis and medicine. The studies of polyaniline (PANI) and other conducting polymers have shown that they possess semiconducting properties. Due to its high stability and unique complex of properties, PANI was the first among conducting polymers to be used in practice as an electrode material for batteries, as a corrosion inhibitor and detecting material for sensors. PANI without dopant material possesses controlled conductivity 10-10 S∙cm-1. PANI was synthesized by the interfacial method by oxidation of aniline with ammonium peroxydisulfate (APS) as an oxidant in an immiscible organic/aqueous biphasic system, with hydrochloric acid as dopant. An organic phase contained aniline dissolved in toluene, while the oxidant was dissolved in acid. The produced PANIs have conductivities in the range 0.03-0.07 S.cm−1. Their nanofiber morphology was confirmed by scanning electron microscopy (SEM). Molecular structure of synthesized PANIs was investigated by FTIR Spectroscopy. DOI :http://dx.doi.org/10.15408/jkv.v0i0.3143